Long-Term Follow-Up of Significant Improvement After CAPTEM Treatment for Rare Adrenocorticotropin-Producing Cardiac Neuroendocrine Tumor - Lu, Lin; Meng, Qingqing; Xing, Xiaoping; Yuan, Tao; Zhang, Huabing; Li, Naishi; Wang, Yining; Cheng, Yuejuan; Bai, Chunmei; Wang, Hao; Cheng, Xin; Xiao, Yu; et al. (Frontiers in Endocrinology, 2019)
Ectopic adrenocorticotropic hormone (ACTH) syndrome (EAS) is a rare cause of Cushing syndrome. If routine imaging examinations cannot identify the source of ACTH production, long-term follow-up observation is necessary to determine the etiology. We present the case of a middle-aged male with gradual weight gain and a Cushingoid appearance over 4 years; he provided written informed consent. Laboratory and endocrine tests strongly suggested EAS, although the origin was not detected by multiple imaging methods. Bilateral adrenalectomy was performed to prevent severe complications in the patient. Two and a half years later, a cardiac mass 18×23×27 mm in size at the junction between the anterior wall of the left ventricle and the middle septum was found together with multiple bone metastases by 18F-FDG PET/CT, while the 68Ga-DOTATE PET/CT findings were negative. Biopsy of the lumbar vertebrae revealed a neuroendocrine tumor (NET) with positive ACTH staining. The patient underwent chemotherapy by CAPTEM, resulting in shrinkage of the cardiac mass and a significant decrease in the ACTH level. In the case of EAS with an unusual cause, long-term follow-up observation is necessary to determine the source of ACTH production. Cardiac NETs are quite rare in EAS, so treatment selection was also challenging. CAPTEM chemotherapy proved effective in controlling the progression of tumor growth and decreasing the ACTH level in this patient.